What a difference does it make ?: understanting the empirical literature on taxation and international captal flows - Mooij, Ruud A. de.; Ederveen, Sjef.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This study explains the variation in empirical estimates in the literature on the elasticity of foreign direct investment with respect to company tax levels. To that end, the meta analysis of De Mooij and Ederveen (2003) is extended by considering an alternative classification of the literature and by including new studies that have recently become available. Specific attention is paid to two new dimensions: the spatial and the time dimension of the underlying studies.
Economic Papers